Experimental thermal energy assessment of a liquid metal eutectic in a microchannel heat exchanger equipped with a (10 Hz/50 Hz) resonator. (5th February 2019) - Sarafraz, M.M.; Hart, J.; Shrestha, E.; Arya, H.; Arjomandi, M.
Highlights: Gallium-indium eutectic was tested in a microchannel equipped with a resonator. The highest HTC was 18, 390 W/m 2 K at Re = 1600 and frequency = 50 Hz for 85%Ga-15%In. The highest thermo-hydraulic performance was 78% for 85%Ga-15%In. Vibration was effective only for eutectics with low concentration of indium (5%). A trade-off was identified between the composition of eutectic and pressure drop. Abstract: In the present work, an experimental investigation was conducted on the fluid flow and heat transfer characteristics of gallium-indium eutectic flowing in the microchannel passages. The overall heat transfer coefficient, pressure drop, friction factor and the thermo-hydraulic performance of the microchannel was experimentally quantified for various compositions of indium in the eutectic mixture. Influence of low-frequency vibration at two frequencies and amplitudes on the overall heat transfer coefficient and thermo-hydraulic performance of the microchannel was also studied and discussed. Results showed that the eutectic mixture has a higher thermal performance in comparison with gallium (78% enhancement in thermo-hydraulic performance). Also, the vibration increased the heat transfer coefficient of the microchannel such that at a frequency of 50 Hz and an amplitude of 10 m/s 2, the highest heat transfer coefficient and thermal performance of the microchannel was registered. However, the effect of the frequency was more tangible for the eutectic mixtures with lower viscosities such as 95%Ga-5%In and pure gallium. Also, neither the frequency nor the amplitude changed the pressure drop value of the system. Interestingly, the presence of the indium in the eutectic mixture enhanced the heat transfer coefficient, which was attributed to the enhancement in the thermal conductivity of the eutectic mixture. The augmentation in the value of the pressure drop was also compensated with the anomalous increase in the heat transfer coefficient. This study revealed the plausible application of Ga-In mixture in high heat flux cooling systems inside the microchannel heat exchangers.